PERSEPSI MASYARAKAT TENTANG PROGRAM KONVERSI MINYAK TANAHKE GAS ELPIJI DI KAMPUNG PASAR BARU KENAGARIAN LAKITAN UTARAKECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Safitri, Winda - (STKIP PGRI Sumbar, 2014)
The focusofthis researchis theproblemofkeroseneto LPGin fillage Pasar Baru Kenagarian LakitanUtara subdistrict Lengayang district Pesisir SelatanThis studyaims to determineanddiscloseindepthaboutpublic perceptionofkerosenetoLPGgas, factorsthatencouragecommunities toimplementprogramsfor kerosene toLPGgas, and thepublic perception of thepost-conversionprogram from kerosene toLPGgas. The research is aqualitativestudy, which was conductedinfillage Pasar Baru Kenagarian Lakitan Utara subdistrict Lengayang district PesisirSelatanInformants in this study is a sub-district head, walinagari, pemungka community, and thecommunity receives LPG feel out were included in the study. Primary data sources include thesearch for information through observation and interviews with informants who have been set.Methods of data collection using observation, interview and documentation. Data analysistechniques through data reduction, data presentation, and decision-making as well as verification.The results showed that the public perception of the conversion program from kerosene to LPGgas is very good, factors that encourage communities to implement programs for kerosene to LPGgas because of the scarcity of kerosene, more economical and efficient in its use and publicperception of the post-conversion program kerosene to LPG gas, the community provides a goodresponse as well.